2011
DOI: 10.1051/radiopro/20116490s
|View full text |Cite
|
Sign up to set email alerts
|

NORM risk assessment for the Søve mining complex, Norway

Abstract: Abstract. The Søve site is a disused mining complex in Telemark County, Norway, exhibiting enhanced levels of naturally occurring radionuclides from the 238 U and 232 Th decay series. The nascent General Assessment Methodology Process ('GAMP'), developed under IAEA's EMRAS II programme, has been applied at the site. The a priori fixed screening criteria were exceeded in the scenario, precipitating the requirement to undertake a more detailed assessment. The USDOE's RESRAD-OFFSITE code was employed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The selection of appropriate remedial options is commonly based on comparison of site-specific data and/or modelling results with pre-defined remediation criteria. An evaluation of remedial options, informed by radioecological data and assessment modelling, has been undertaken for the Søve former niobium (Nb) mining site in Norway, which exhibits enhanced levels of naturally occurring radionuclides from the 238 U and thorium-232 ( 232 Th) decay series (Brown et al 2011). Although some remediation work was conducted following the closure of the mine in the mid-1960s, radioactive waste mixed with surface soils over time and, consequently, high NORM activity concentrations in soil, elevated gamma dose rates and radon levels have been measured at the site (Mrdakovic Popic et al 2011, 2012.…”
Section: Supporting the Evaluation Of Different Remedial Options Thei...mentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of appropriate remedial options is commonly based on comparison of site-specific data and/or modelling results with pre-defined remediation criteria. An evaluation of remedial options, informed by radioecological data and assessment modelling, has been undertaken for the Søve former niobium (Nb) mining site in Norway, which exhibits enhanced levels of naturally occurring radionuclides from the 238 U and thorium-232 ( 232 Th) decay series (Brown et al 2011). Although some remediation work was conducted following the closure of the mine in the mid-1960s, radioactive waste mixed with surface soils over time and, consequently, high NORM activity concentrations in soil, elevated gamma dose rates and radon levels have been measured at the site (Mrdakovic Popic et al 2011, 2012.…”
Section: Supporting the Evaluation Of Different Remedial Options Thei...mentioning
confidence: 99%
“…Although some remediation work was conducted following the closure of the mine in the mid-1960s, radioactive waste mixed with surface soils over time and, consequently, high NORM activity concentrations in soil, elevated gamma dose rates and radon levels have been measured at the site (Mrdakovic Popic et al 2011, 2012. Three remedial options were selected for evaluation (Brown et al 2011): (1) no action, if assessment indicated no need for clean-up; (2) a local countermeasure solution that would involve removal of materials and re-disposal in the area originally allocated for the waste disposal; or (3) complete removal of radioactive waste and disposal at an approved repository.…”
Section: Supporting the Evaluation Of Different Remedial Options Thei...mentioning
confidence: 99%
See 1 more Smart Citation